From Green Accounting To Green Villages: The Role Of Village-Owned Enterprises In Realizing SDGs - Lisna Lisnawati; Suparjiman (Jurnal Reviu Akuntansi dan Keuangan, 2026)
Purpose: This research aims to develop a green accounting model in Village-Owned Enterprises (V-OEs), develop grounded theory, and see its impact on village SDGs to be able to realize a green village. Methodology/approach: This research employed a qualitative approach based on grounded theory, with data collection using triangulation. The research subjects were the Sugih Mukti and Margamakmur V-OEs, which were categorized as advanced V-OEs by the Ministry of Villages. Findings: This study provides a clear reference regarding the feasibility of developing green accounting in V-OEs by presenting environmental financial accounts and reports. This study also successfully developed a grounded theory—public sector sustainability theory, demonstrating that V-OEs' existence impacts village SDGs and can encourage the creation of green villages. Practical implications: The theoretical implications of this research extend the theories presented—public sector sustainability theory, integrating QBL and Institutional Theory—in the context of V-OEs. Empirical implications include presenting a green accounting model for V-OEs, which has been proven to be implementable. Implications for the government include providing a basis for developing green accounting in the broader public sector. Originality/value: V-OEs Green Accounting Model and Public Sector Sustainability Theory.